New missions of a hospital pharmaceutical technology unit during the COVID-19 pandemic - Alexandra Garnier; Ludivine Falaschi; Pascal Bonnabry; Lucie Bouchoud (Taylor & Francis Group, 2021)
The pharmaceutical technology unit of the Geneva University Hospitals played a significant role in the fight against COVID-19 through four different missions: (1) providing enough hydroalcoholic solution at the peak of the pandemic; (2) facing supply chain management issues; (3) adapting the workload to the crisis and, above all, (4) managing the human resources necessary to handle these activities.